2003
DOI: 10.1002/iroh.200390035
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Coarse Particulate Organic Matter on the Sediments of Njoro River, Kenya

Abstract: Retention of benthic organic matter (BOM) on the sediment surface of the Njoro River, Kenya was investigated between February 1998 and June 1999 at two sites, differing in channel morphology and riparian vegetation density and composition i.e. open-canopy and closed-canopy sites. Monthly accumulation of benthic organic matter (BOM) was highly variable, ranging from 97.3 to 6691.8 and from 206.6 to 1936.3 g ash free dry weight m -2 (AFDW) with a mean ± CL of 1133.3 ± 794.5 and 834.9 ± 275.8 g AFDW m -2 at the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Riparian plant species lose their leaves during different periods of the year and riverine characteristics of the studied stretch (bank inclination and stability, soil type, seasonal discharge, etc.) would influence the direction and location where the allochthonous organic matter deposits (Fleituch, 2001, Artmann et al, 2003, Magana and Bretschko, 2003. Our findings also suggested that major stocks of organic matter from soil were transferred to the stream.…”
Section: Discussionsupporting
confidence: 55%
“…Riparian plant species lose their leaves during different periods of the year and riverine characteristics of the studied stretch (bank inclination and stability, soil type, seasonal discharge, etc.) would influence the direction and location where the allochthonous organic matter deposits (Fleituch, 2001, Artmann et al, 2003, Magana and Bretschko, 2003. Our findings also suggested that major stocks of organic matter from soil were transferred to the stream.…”
Section: Discussionsupporting
confidence: 55%
“…Also the bank slope is an important factor influencing the amount of litter in the humid zones (e.g. HILL and BROOKS, 1996;MAGANA and BRETSCHKO, 2003;MOSER, 1994). Although the downstream site has gentle slopes, the amounts of CPOM in the humid zones here were lower than in the upstream site.…”
Section: Discussionmentioning
confidence: 94%
“…A pilot study established the need for longer time scales than those used in the majority of published studies (e.g. Boulton & Boon, 1991;Magana & Bretschko, 2003;Banuelos et al, 2004), with leaves not moving from the upstream pool until after rain. A 4-mm mesh net was anchored to the stream bed at the downstream end of each study reach.…”
Section: Survey Of Retention Structuresmentioning
confidence: 99%